2023
DOI: 10.2147/rmhp.s398826
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of MRI Safety Practices in Saudi Arabia

Abstract: Aim The aim of this study is to investigate the safety practices used by MRI departments in Saudi Arabia. Methods A cross-sectional study across 113 private and public hospitals was conducted in Saudi Arabia. A survey questionnaire was designed and sent to 113 MRI units. The questionnaire consisted of 43 items under 14 sections for the assessment of MRI safety practices. These 14 sections are related to (i) MRI and its safety, (ii) MRI usage and its safety, and (iii) sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This variation suggests that there may be significant discrepancies in the quality and consistency of anesthesia care provided across different units and institutions. Addressing this variability is of paramount importance for promoting standardized and optimal anesthesia practices throughout Saudi Arabia [ 8 , 13 ]. The study’s findings also shed light on the compliance rates regarding guidelines for anesthesia administration in MRI environments, revealing interesting patterns among different types of hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This variation suggests that there may be significant discrepancies in the quality and consistency of anesthesia care provided across different units and institutions. Addressing this variability is of paramount importance for promoting standardized and optimal anesthesia practices throughout Saudi Arabia [ 8 , 13 ]. The study’s findings also shed light on the compliance rates regarding guidelines for anesthesia administration in MRI environments, revealing interesting patterns among different types of hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate these risks, comprehensive guidelines and protocols for anesthesia administration in MRI settings have been developed to enhance patient safety and optimize the quality of imaging results. The Association of Anaesthetists in the UK published guidelines in 2002, with an update on the safety of MR units in 2019 [ 6 , 7 , 8 , 9 ]. Furthermore, the American Society of Anesthesiologists released a practice advisory providing specific recommendations for safe anesthesia administration in MRI environments [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent assessment of magnetic resonance imaging (MRI) safety practices in Saudi Arabia has revealed that the majority of MRI units have demonstrated compliance with most of the safety recommendations; nonetheless, there are a few main items for which the guidelines may not be attained, like the absence of specialists and regular training programs to improve MRI safety practices for both patients and health care workers (Alghamdi 2023). [ 5 ]…”
Section: Introductionmentioning
confidence: 99%